2020
DOI: 10.1111/pace.14042
|View full text |Cite
|
Sign up to set email alerts
|

Bradyarrhythmias in patients with COVID‐19: Marker of poor prognosis?

Abstract: Background: Despite descriptions of various cardiovascular manifestations in patients with coronavirus disease 2019 (COVID-19), there is a paucity of reports of new onset bradyarrhythmias, and the clinical implications of these events are unknown. Methods: Seven patients presented with or developed severe bradyarrhythmias requiring pacing support during the course of their COVID-19 illness over a 6-week period of peak COVID-19 incidence. A retrospective review of their presentations and clinical course was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 14 publications
1
60
0
2
Order By: Relevance
“…Of course, pulmonary hypertension, severe acute respiratory distress syndrome, and heart failure that strain the right ventricle can each predispose a patient to an increased risk of arrhythmias. 3 , 4 However, our echocardiogram did not reveal a significant dilation in her chamber. Other causes, like myocardial ischemia and electrolyte imbalance, were excluded, given the lack of new regional wall motion abnormality, normal troponin levels, brain natriuretic peptide, and normal electrolytes.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Of course, pulmonary hypertension, severe acute respiratory distress syndrome, and heart failure that strain the right ventricle can each predispose a patient to an increased risk of arrhythmias. 3 , 4 However, our echocardiogram did not reveal a significant dilation in her chamber. Other causes, like myocardial ischemia and electrolyte imbalance, were excluded, given the lack of new regional wall motion abnormality, normal troponin levels, brain natriuretic peptide, and normal electrolytes.…”
Section: Discussionmentioning
confidence: 58%
“…The potential underlying mechanisms include hypoxia, autonomic dysregulation, myocarditis, exaggerated immune response (eg, cytokine storm), myocardial stretch, myocardial ischemia, electrolyte imbalances, intravascular volume depletion, and drug-induced side effects. 3 Unfortunately, there is a paucity of research on bradyarrhythmias among COVID-19 patients (compared with tachyarrhythmias), 4 and bradyarrhythmia indicates a poor prognosis, even without coexistent acute cardiac injury. 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic impact of sinus pauses in COVID‐19 infection is not well known due to the relative paucity of reported cases. While asymptomatic cases that have been described in the literature till date seem to have recovered from the infection [ 3 - 4 ], most of the reported cases with symptomatic sinus node dysfunction associated with COVID‐19 have had poor prognosis despite permanent pacemaker implantation [ 9 ]. This could indicate the need for aggressive treatment and intensive monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Wuhan reported the frequency of acute myocardial damage about 7.2% and cardiac arrhythmias about 16.7%. However, severe bradyarrhythmias such as third-degree atrioventricular block (AVB) have been relatively uncommon [ 2 ]. Herein, we have described the clinical presentation of advanced AVB in a patient with uncomplicated COVID-19 infection, which persisted over 4 weeks without hemodynamic instability.…”
Section: Introductionmentioning
confidence: 99%